Market Penetration Strategy for Traditional Beverage Products: A Case Study of Bugis-Makassar's Typical Sarabba - Ayu Putriana Dewi; Agung Winarno (International Journal of Economics, Commerce, and Management, 2025)
In the midst of increasingly fierce modern market competition, traditional beverage products such as sarabba from Makassar began to enter the competitive market. This study aims to analyze the market penetration strategy of Makassar's Sarabba traditional beverage product in an effort to expand its reach and increase competitiveness in local and national markets. Sarabba, as a traditional spice-based drink, has high cultural value and economic potential but faces challenges in terms of marketing and adaptation to modern consumer tastes. The research method used is a qualitative approach with a case study, through direct observation, interviews with business actors, and documentation analysis. The results showed that the market penetration strategy implemented includes product innovation in the form of ready-to-eat packaging, utilization of digital media for promotion, and collaboration with local MSMEs and creative industry players. With the implementation of effective marketing strategies (4P), Saraba can maintain its traditional flavors while reaching new consumers in local and national markets. This research contributes to the development of marketing strategies for traditional products and suggests ways to improve the competitiveness of local products in the international market. This strategy is considered effective in increasing the visibility of Sarabba products among the younger generation and tourists. This research suggests the need for local government support in the form of training, product certification, and market access facilitation to strengthen Sarabba's existence as a competitive local culinary identity in the era of globalization.